2020
DOI: 10.3390/molecules25040984
|View full text |Cite
|
Sign up to set email alerts
|

The Plasma Spectroscopic Study of Dergaon Meteorite, India

Abstract: Meteorites are the recoverable portions of asteroids that reach the surface of the Earth. Meteorites are rare extraterrestrial objects studied extensively to improve our understanding of planetary evolution. In this work, we used calibration-free laser-induced breakdown spectroscopy (CF-LIBS) to evaluate the quantitative elemental and molecular analyses of the Dergaon meteorite, a H 4-5 chondrite fall sample from Assam, India. Spectral signatures of H, N, O, Na, Mg, Al, Si, P, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CF-LIBS method has been used to investigate the elemental concentration of lighter elements H, N, O. Along with atomic lines, molecular emissions of FeO has also been observed in this study [53]. Laser-induced breakdown spectroscopy has been developed for robotic vehicles and successfully implemented in planetary exploration from the past few years.…”
Section: Application Of Libs For the Extraterrestrial Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…CF-LIBS method has been used to investigate the elemental concentration of lighter elements H, N, O. Along with atomic lines, molecular emissions of FeO has also been observed in this study [53]. Laser-induced breakdown spectroscopy has been developed for robotic vehicles and successfully implemented in planetary exploration from the past few years.…”
Section: Application Of Libs For the Extraterrestrial Analysismentioning
confidence: 90%
“…Also, concentration profiles for major elements Fe, Ni, and Co have been detected for iron meteorite Toluca. The Dergaon Meteorite has been studied by Rai et al (2020). CF-LIBS method has been used to investigate the elemental concentration of lighter elements H, N, O.…”
Section: Application Of Libs For the Extraterrestrial Analysismentioning
confidence: 99%
“…Tempesta et al 138 applied CF-LIBS for the μ-LIBS analysis of an iron meteorite found in Russia in 2000, while Rai et al 139 performed by CF-LIBS the spectrochemical characterization of moldavite, a glass originating from a meteorite impact. The same group 140 determined the concentration of Ni, Cr, Co and Ir in the Dergaon meteorite, in India, thus assessing CF-LIBS as a promising analytical tool in view of future application of LIBS in in situ analysis of extra-terrestrial objects and in planetary rover missions.…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, we need a profound technique to overcome all these drawbacks in the above-discussed analytical tools for rapidly identifying and classifying metallic alloy-based objects. Recently, LIBS has emerged as a more effective tool for compositional analysis and identification/classification of materials/alloys used in producing different objects/coins [20][21][22][23][24][25][26][27][28][29][30]. Because of its ability of in situ, quasi-non-destructive, and no/minimal sample preparation, we can use this technique to identify and classify metallic alloys in different fields like archaeology and precious metallic alloys/coins.…”
Section: Introductionmentioning
confidence: 99%